WORD MAPPING IN STUDENTS’ VOCABULARY MASTERY - Qomariyah, Siti Syafi'atul; Nafisah, Bq. Zuhrotun (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
This research was aimed to find out the effect of word mapping strategy in students? vocabulary mastery. The research was experimental research. The population was the second-grade students of SMP Islam Al-Azhar NW Kayangan which consisted of two classes (60 students). This research used total sampling technique to select the samples VIII.1 class (30 students) as the experimental group and VIII.2 class (30 students) as the control group. This research applied word mapping strategy at experimental group and word wall strategy at control group as treatment. In treatment process, the researchers found that the students were interested when the teacher applied word mapping strategy. The teacher was not only focused on the material but also guided the students to be more interactive in teaching and learning process. To analyze the data, the researchers used descriptive and inferential statistics. The result of data analysis showed that t-test 7.171 with t-table 1.672at the level of significance 0.50, it was shown that t-test was higher than t-table. On the other words, the hypothesis was accepted.